Effects of putrescine on gene expression in relation to physical barriers and antioxidant capacity in organs of weaning piglets. Issue 34 (24th June 2019) - Liu, Guangmang; Mo, Weiwei; Xu, Xiaomei; Wu, Xianjian; Jia, Gang; Zhao, Hua; Chen, Xiaoling; Wu, Caimei; Wang, Jing
Abstract : Weaning stress can cause metabolic disorders, gastrointestinal dysfunction, physical barrier injury and disease susceptibility, thus leading to impaired growth and health of animals. Abstract : Weaning stress can cause metabolic disorders, gastrointestinal dysfunction, physical barrier injury and disease susceptibility, thus leading to impaired growth and health of animals. Putrescine has the potential to reduce stress effects. However, the role of putrescine supplementation on barrier function and antioxidant capacity in animals' organs is largely unknown. This study evaluates the effects of putrescine on the physical barrier function, antioxidant status and related signalling molecule levels of weaning piglets' organs. A total of 24 weaning piglets were assigned to four treatment groups: (1) basal diet (control) and basal diets supplemented with (2) 0.05%, (3) 0.1% and (4) 0.15% putrescine. At the end of the 11 day experiment, ileum, liver, thymus and spleen samples were collected from the piglets. Compared with the control group, 0.15% putrescine can significantly increase anti-hydroxyl radical capacity (ileum and spleen), anti-superoxide anion capacity (liver, thymus and spleen), catalase (ileum, liver, thymus and spleen), total superoxide dismutase (ileum, thymus and spleen), glutathione peroxidase (ileum, liver and thymus), glutathione S -transferase activity (ileum, liver, thymus and spleen), glutathione content (liver and spleen) and total antioxidant capacity (ileum and thymus); decrease malondialdehyde (ileum, liver, thymus and spleen), protein carbonyl content (ileum, liver, thymus and spleen); enhance mRNA expression of zonula occludens (ZO)-1 (spleen), ZO-2 (liver, thymus and spleen), occludin (ileum, liver, thymus and spleen), claudin 1 (ileum, liver, thymus and spleen), claudin 2 (ileum, thymus and spleen), claudin 3 (ileum, liver, thymus and spleen), claudin 14 (ileum, liver and spleen), claudin 16 (ileum and liver), superoxide dismutase 1 (ileum, liver and thymus), glutathione peroxidase 1 (ileum, liver, thymus and spleen), catalase (ileum, liver, thymus and spleen), glutathione reductase (thymus and spleen), glutathione S -transferase (ileum, liver, thymus and spleen) and nuclear erythroid 2-related factor 2 (liver and thymus); decrease mRNA level of myosin light chain kinase (ileum, liver, thymus and spleen) and Kelch-like ECH-associated protein 1 (liver and spleen) ( P < 0.05). 0.05% putrescine can significantly affect some of the above-mentioned parameters ( P < 0.05). Collectively, putrescine supplementation improves organs' physical barrier function and antioxidant capacity in dose- and tissue-dependent and independent effects; such improvements are beneficial to the health of weaning piglets.